High School Students' Scientific Argumentation Skills on Static Fluid - Ivan Danar Aditya Irawan; Sarah Lutfiah Ardilla; Sayyidah Assadillah Almujaddid; A. Syafriyana (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2025)
The need to improve students' argumentation skills through phenomenology learning approaches encourages efforts to map scientific argumentation skills. the research aims to determine students' argumentation skills on static fluid. Qualitative research with survey method using questions about static fluid phenomena in everyday life. random sampling obtained 33 students from one of the State High Schools in Malang Regency as samples in the study. Data were analyzed by mapping the level of scientific argumentation skills. The results showed that students' argumentation skills were spread from level 1 to level 4 with the majority at level 2. At this level, students are generally able to provide claims consisting of data and reasoning. This achievement shows that students' scientific argumentation skills are relatively low. Future research can design innovative models and media to improve students' scientific argumentation skills.